THE REPRESENTATION OF WOMEN SCIENTIST IN AGORA - Rahayu, Mundi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
The research aims to explore the representation of woman scientist in film Agora. Agora is a film focusing on the life of a woman scientist and philosopher named Hypatia who lived in Alexandria at the end of 4th A.D.Â The research uses semiotics that is applied to explore the signs and the meaning of the film. The signs are in the forms of visual and verbal signs, such as the image, dialogue, setting of place, plot, character, narration, etc. The result of the analysis shows that Hypatia is represented as a legend in astronomy and philosophy who dedicated all her life for science. Beside represented as a scientist, Hypatia is also an icon of sexual freedom though her choice for not getting married. She wants to make sure that she gets her liberty as any other man so that she is able to pursue the knowledge. Her reputation as a scientist, a rationalist, a skeptics bring her into her own symbolical power. Such symbolical power and unwillingness to subjugate to the dominant power leads her to her tragic end of her life. Hypatia is one of the first victims in the clash of science and the intolerance of religion. Though some historical inaccuracy, the films shows that the film maker confidently made a particular interpretation on the history. The social cultural setting of the story is on the rise of Christianity and the fall of Paganism in Alexandria at the end of 4 AD. This culminated in the destruction of the famous Library of Alexandria, where the largest part of the ancient Greek knowledge in mathematics, astronomy, philosophy and literature was preserved.Keywords: Agora, Hypatia, Representation of Woman, Alexandria, Pagan